An approach to assessing the quality of transport service in road logistics - Ptytsia N.; Птиця, Наталія Василівна (Харківський національний автомобільно-дорожній університет, 2025)
The study addresses the problem of terminological ambiguity and methodological inconsistency in defining and assessing transport service provision in road freight transportation. In practice, the concepts of transport service and transport service provision are often used interchange-ably, which leads to incorrect managerial decisions, fragmented quality assessment, and inefficiencies in logistics processes. The need to clarify the structure of transport service provision, determine its components, and establish measurable indicators is intensified by the growing complexity of logistics systems and increasing customer expectations for reliability, flexibility, and transparency of transport operations. Goal. The aim of the work is to develop a structured and theoretically substantiated framework for interpreting transport service provision and to justify methodological approaches for evaluating its quality in road freight transport. Methodology. The methodology is based on critical analysis of scientific literature, systematization of regulatory definitions, decomposition of the service provision structure into transport output, transport process, and customer interaction, as well as ex-amination of modern tools for transport planning, routing optimisation, and digital support of logis-tics processes using TMS, GIS, and algorithmic methods. Results. The results demonstrate that transport service provision should be interpreted as a complex process encompassing preparation, organization, execution, and coordination of freight transportation, while a transport service repre-sents the final result of this process. Originality. The proposed structured framework enables the iden-tification of quality indicators relevant to different stages of transportation and enhances objectivity in evaluating logistics performance. The originality of the study lies in substantiating the procedural in-terpretation of transport service provision, distinguishing it from the concept of transport service, and demonstrating the integrative role of digital tools and routing algorithms in improving service quality. Practical value. The practical value is reflected in the possibility of applying the developed approach to optimize transport operations, reduce empty mileage, improve fleet utilization, increase delivery reliability, and support evidence-based decision-making in transport companies. This contributes to strengthening the competitiveness of road freight carriers under modern market conditions.
Підхід до оцінювання якості транспортного обслуговування в автомобільній логістиці
Keywords: transport service provision; service quality; road freight transportation; routing optimization; logistics efficiency; TMS; GIS; надання транспортних послуг; якість транспортного обслуговування; автомобільні вантажні перевезення; оптимізація маршрутів; логістична ефективність; 656.1; 10.30977/AT.2219-8342.2025.57.0.08